Excited State Dynamics of Methylated Guanosine Derivatives Revealed by Femtosecond Time‐resolved Spectroscopy. (4th March 2022) - Wang, Danhong; Wang, Xueli; Jiang, Yanrong; Cao, Simin; Jin, Peipei; Pan, Haifeng; Sun, Haitao; Sun, Zhenrong; Chen, Jinquan
Abstract: Methylated DNA/RNA nucleobases are important epigenetic marks in living species and play an important role for targeted therapies. Moreover, methylation could bring significant changes to the photo‐stability of nucleic acid, leading these sites become mutational hotspots for disease such as skin cancer. While a number of studies have demonstrated the relationship between excited state dynamics and the biological function of methylated cytosine in DNA, investigations aimed at unraveling the excited state dynamics of methylated guanosine in RNA have been largely overlooked. In this work, influence of methylation on the excited state dynamics of guanosine is studied by using femtosecond time‐resolved spectroscopy. Our results suggest that the effect of methyl substitution on the photophysical properties of guanosine is position sensitive. N1‐methylguanosine shows very similar excited state dynamics as that in guanosine, while almost one order of magnitude longer lifetime of the La state is observed in N2, N2‐dimethylguanosine. Notably, N7‐methylation can lead to a new minimum on the La state and the excited state lifetime is two orders of magnitude longer than that of guanosine. These findings not only help understanding excited state dynamics of methylated guanosines, but also lay the foundation for further studying DNA/RNA strands incorporated with these bases. Abstract : The photophysical and photochemical properties of methylated guanosine are studied. Ultrafast deactivation of the excited state are observed in N1‐methylguanosine and N2, N2‐dimethylguanosine. On the other hand, longer lived decay pathway is found in N7‐methylguanosine.